Hausväterliteratur in the Educationand Spirituality of a Noblemanin the Early Modern Era - Rychnová, Lucie; Akimjaková, Beáta; Judák, Viliam; Hlad, Ľubomír; Ďatelinka, Anton (Journal of Education Culture and Society, 2022)
Aim. The aim of this study is to discuss how important the so-called Hausväterliteratur genre was in the education and spirituality of (not only) aristocrats in the Early Modern Era.Concept. This article will introduce the Hausväterliteratur as a literary genre that strongly influenced the spirituality and morality of its readers –householders, administrators of property, and their wives.Methods. The method applied was text analysis. The social history method based on research of the primary sources was also employed..Results. The study confirms that the treatises of the so-called Hausväterliteratur genre, kept in high numbers in European libraries in the Early Modern Age, carry a certain type of spirituality which calls for “true Christian life” following what was often a Protestant pattern (exhortation for frequent reading of the Bible).Conclusion. Most of these books outline an ideal of the Christian life, characterised by the establishment of an order within the “household”, or “house”, i.e., the family in the broader sense, including both the manor owner and those closest to him as well as all his subjects and servants.